54 UNEXPLAINED CARDIAC TAMPONADE. (1st January 2006) - Shetty, S.; Sahni, A.; Sinnapunayagam, S.; Thelusmond, H.; Khanna, A.
Abstract : A 28-year-old Hispanic woman came to the Coney Island Hospital ER with gradually progressive distention of the abdomen, shortness of breath, puffiness of the face, and swelling of her feet for 1 month. There was loss of appetite with a weight loss of approximately 20 pounds occurring over 1 month. In the ER, the patient had a temperature of 988F, a pulse of 90 to 100 per minute, regular but thready, a blood pressure 110/70 mm Hg with no Kussmaul's sign, and a respiratory rate of 18-20 per minute. She had jugular venous distention with distant soft heart sounds but no murmurs or pericardial rub. Lung fields were clean and the abdomen revealed a mild ascites. There was no calf asymmetry. Peripheral pulses were feeble. Laboratory data revealed a normal total white count with normal differential. Serum chemistry including electrolytes, renal and liver function tests were normal. ESR, amylase, and lipase were normal. CPK was normal and pregnancy test was negative. The electrocardiogram was low voltage with electrical alternans at a rate of 86 bpm, normal axis, P-R interval 134 ms, Q-T 336/402 ms, and QRS was 78 ms.Chest x-ray revealed an enlarged, globular heart. A CT scan of the chest was done, which showed a large pericardial effusion. A bedside echocardiogram revealed a large pericardial effusion with diastolic collapse of the right ventricle. The patient was admitted to the cardiac intensive care unit and a pericardiocentesis was done; 1.5 L of bloody fluid drained in pericardial tap, which was hemorraghic, with 44% PMN, 55% lymphocytes, a negative gram and acid-fast stains, and adenosine deaminase of 16. The histopathology was acellular fluid negative for malignancy. Serum for ECHO and coxsackievirus 1-6 were negative. A pericardiectomy with pericardial window was done to prevent reaccumulation of the pericardial effusion. The pericardial biopsy showed acute fibrinous and chronic nonspecific pericarditis. PPD was negative. The pericardial tissue culture was negative for bacteria including Mycobacterium tuberculosis. A search for occult malignancy was begun and the patient was found to have a raised CA 125. Her Pap smear showed grade 1 CIN and cone biopsy, which showed squamous metaplasia but no dysplastic changes. A CT abdomen showed bilateral ovarian cysts, which were biopsied laparoscopically and found negative for malignancy. Collagen vascular work-up and HIV testing were negative. The patient recovered from the acute illness and was followed up by pulmonary, oncology and gynecology but no malignancy could be detected.